Analysis of the use of phase change materials to improve building energy efficiency and thermal energy storage - Lazariev, Yevhen; Sukhodub, Iryna (Technologies and Engineering, 2025)
The growing demand for energy-efficient buildings and the need to reduce greenhouse gas emissions necessitate the adoption of innovative approaches to thermal energy management in buildings. One such approach involves the use of phase change materials, which enable thermal energy storage and increase the thermal inertia of building structures. This makes them an effective solution for optimising energy efficiency under varying climatic conditions. This article aimed to analyse existing methods of employing phase change materials to enhance the energy efficiency of buildings through thermal energy storage. In particular, the study focused on techniques for incorporating these materials into building envelopes and their application in thermal storage systems. The article applied methods of analysis and synthesis of scientific literature, with particular attention given to studies on the impact of phase change materials on the thermal inertia of building components, their effectiveness in thermal energy storage units, and their influence on overall building energy performance. It has been established that the use of phase change materials significantly increases the thermal inertia of buildings and reduces heat loss. Various methods of incorporating phase change materials into building envelopes and their application in thermal storage systems have been analysed. The main advantages and drawbacks of each method have been identified, along with examples of their practical implementation. Potential uses of thermal storage units for enhancing building energy efficiency have been outlined, particularly their integration into heating and domestic hot water systems. The findings of the study may be applied in the design of energy-efficient buildings and heating and hot water supply systems that utilise phase change materials for thermal energy storage. This contributes to lower energy consumption and improved living comfort